Did an official qualification known as ministrante really exist? - José Antonio Ávila Olivares (Universidad de Alicante, 2012)
It is accepted in Spanish nursing history the existence of the figure of 'Ministrante' as a professional antecendent of current nurses. This new professional arose with the enactment of the Royal Order of 29th June 1846, which later lead up to The Public Instruction Act of 9th September 1857, known as the Moyano Act by which the qualification of "practicante" was created. But, did an official qualification of "ministrante" really exist? The research carried out and the information gathered shows that it did not. The name of Minor Surgeon or 'Ministrante' was given to a professional, social and even institutional category who was the previous Blood-letter but with a new education syllabus. However, we are sure this would be a new field for further research in nursing history.